2014
DOI: 10.1200/jco.2014.32.26_suppl.135
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of BRCA 1/2-mutated (BRCA+) and triple-negative, BRCA wild type (BRCA-wt) breast cancer patients in a phase I study of single-agent veliparib (V).

Abstract: 135 Background: Veliparib (V) (ABT-888) is an oral, potent inhibitor of PARP 1/2. PARP inhibitors have preclinical and clinical efficacy in BRCA+ malignancies. There are genotypic and phenotypic similarities between BRCA+ cancers, serous ovarian cancer and basal-like breast cancer and we postulated that these tumors types may be similarly sensitive to single-agent PARP inhibition. This study sought to establish the maximum tolerated dose (MTD), dose -limiting toxicities (DLT), pharmacokinetic and pharmocodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…These results are consistent with other veliparib studies in which patients with BRCA wild-type TNBC experienced objective tumor response (13, 47). Patients whose carcinomas had a basal phenotype by IHC did not have better responses than patients with non-basal-like TNBCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with other veliparib studies in which patients with BRCA wild-type TNBC experienced objective tumor response (13, 47). Patients whose carcinomas had a basal phenotype by IHC did not have better responses than patients with non-basal-like TNBCs.…”
Section: Discussionsupporting
confidence: 92%
“…This is significant because there is evidence for a dose response relationship with veliparib, and single agent activity is observed beginning at 300 mg BID (13). In germline BRCA mutation-associated cancer, a recently completed phase I study evaluated 9 dose levels of veliparib monotherapy and demonstrated a 29% overall response rate (at all dose levels combined) and a higher response rate of 60% at the RP2D (47). The finding of higher clinical response rates with higher doses of veliparib, despite achieving 90% PARP inhibition at lower doses by PAR assay (12, 13) suggests that combinations which allow for higher PARP inhibitor dosing may be preferred in order to achieve the best therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence demonstrate that PARPis potentiate the effects of platinum in vivo (1317) and emerging data suggest synergism between PARPis and platinum compounds in BRCA -associated BCs (1820). Consequently, the California Cancer Consortium conducted companion clinical trials in patients with BRCA -associated MBC.…”
Section: Introductionmentioning
confidence: 99%
“…Responses to PARP-inhibitors have also been reported in patients with sporadic high grade serous ovarian carcinoma [27] and triple negative breast cancer [24]. Tumor responses to PARP-inhibitors in the BRCA1 and BRCA2 wild-type population may be related to other types of HRD.…”
Section: Homologous Recombination Dna Repairmentioning
confidence: 98%
“…In breast cancer patients with germline BRCA1/ BRCA2 mutations, the reported response rate with PARP-inhibitors (olaparib, veliparib, niraparib and BMN-673) ranges from 13-55%, with greater clinical benefit in the triple negative subgroup [22][23][24][25][26][27]. Based on these promising results, Phase III clinical trials in advanced breast cancers in patients with germline BRCA1/2 mutations have started with the four PARP-inhibitors: olaparib (OLYMPIA trial, NCT02000622), veliparib (NCT02163694), niraparib (BRAVO trial, NCT01905592) and BMN 673 (EMBRACA trial, NCT01945775).…”
Section: Homologous Recombination Dna Repairmentioning
confidence: 99%